Declining agriculture in Garhwal Himalaya: Major drivers and implications - Vishwambhar Prasad Sati; Saurav Kumar (Cogent Social Sciences)
Subsistence agriculture—the cultivation of subsistence cereals including millets, oilseeds, and pulses is the major occupation and source of livelihood of people of the Garhwal region. Over time, the production and yield of subsistence agriculture have reduced drastically. This study examines the practices of subsistence agriculture, the major drivers of declining agriculture, and its implications on the livelihood of marginal farmers. Data were gathered from eight villages of four districts, using a household-level survey. A total of 376 households inhabit these villages. We have surveyed 207 households (55%), who were fully engaged in practicing subsistence agriculture, purposively. A structured questionnaire was constructed and the questions were asked from the heads of households on the area, production, and productivity of the principal crops during 2000–2020. Data were analyzed using statistical methods. This study depicted that traditional agriculture has been declining, as a 50% decrease in the area, production, and productivity of crops was noticed during the last 20 years. The decrease was noted mainly due to climate change, extreme geo-hydrological disasters, crops damaged by wildlife, increasing population, decreasing landholdings, low soil fertility, low output from arable land, mono-cropping, and a lack of use of modern technology. The exodus out-migration, land abandonment, and livelihood insecurity were noticed as the implications of declining subsistence agriculture.